Implementation of digital tachograph system in european union - Rychter, M. (BNTU, 2010)
Tachograph belongs to On Board Recording Devices. It was initially introduced for the railroads in order to companies could better document irregularities. The inventor of the tachograph was Max Maria von Weber, an administrative official, engineer and author. The Hasler Event Recorder was introduced in the 1920s. Regrettably, the construction of analogue tachograph, an original type of tachograph used in road transport, encouraged to numerous frauds and counterfeits of social rules for drivers. For this reason the European Union has developed an inspection system, based on digital ta-chograph and chip cards, used for recording the data and identification of the system users. The article is the presentation of the main rules of function of the digital tachograph system, used in road transport in European Union. The document describes main legal rules introducing the digital tachograph sys-tem, foremost requirements which must be fulfilled by the producers of digital tachographs in order to get the type approval, possibility of future requirements of digital tachograph, main functions, charac-teristics of participant of digital tachograph system and their tools of the identification, acting and set-ting of authorize workshops in Poland and European Union and the accessible methods of check and calibration of digital tachographs and their description, based on Commission Regulation (EC) No 1360/2002 of 13 June 2002. Furthermore, the dissertation presents current level of implementation of digital tachograph system in EU Member States.